2006
DOI: 10.1186/1476-7120-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular free wall impeding rupture in post-myocardial infarction period diagnosed by myocardial contrast echocardiography: Case report

Abstract: Background: Left ventricular free wall rupture occurs in up to 10% of the in-hospital deaths following myocardial infarction. It is mainly associated with posterolateral myocardial infarction and its antemortem diagnosis is rarely made. Contrast echocardiography has been increasingly used for the evaluation of myocardial perfusion in patients with acute myocardial infarction, with important prognostic implications. In this case, we reported its use for the detection of a mechanical complication following myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Unfortunately, this distinction is rarely mentioned since echocardiogram and angiography are not always able to distinguish between the two anatomical entities [7]. Recently, some authors have demonstrated that contrast echocardiography might be helpful to delineate the defect [8]. …”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, this distinction is rarely mentioned since echocardiogram and angiography are not always able to distinguish between the two anatomical entities [7]. Recently, some authors have demonstrated that contrast echocardiography might be helpful to delineate the defect [8]. …”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis is usually made with conventional echocardiography, while echocardiographic contrast can show the exact localization of the rupture [10]. …”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] In our patient with acute LVFWR, rapid confirmation of the diagnosis was aided by the use of bedside contrast-enhanced echocardiography, and by our cardiologists' familiarity with this diagnostic method in the care of a critically ill patient. Furthermore, this case highlights the acute nature of mechanical sequelae of MI, particularly because reperfusion therapy was not administered.…”
Section: Discussionmentioning
confidence: 95%